2010
DOI: 10.1111/j.1365-313x.2010.04191.x
|View full text |Cite
|
Sign up to set email alerts
|

Histone hyperacetylation affects meiotic recombination and chromosome segregation in Arabidopsis

Abstract: SUMMARYIn this study, the meiotic role of MEIOTIC CONTROL OF CROSSOVERS1 (MCC1), a GCN5-related histone N-acetyltransferase, is described in Arabidopsis. Analysis of the over-expression mutant obtained by enhancer activation tagging revealed that acetylation of histone H3 increased in male prophase I. MCC1 appeared to be required in meiosis for normal chiasma number and distribution and for chromosome segregation. Overall, elevated MCC1 did not affect crossover number per cell, but has a differential effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 72 publications
(162 reference statements)
4
49
0
Order By: Relevance
“…It has been reported that the expression of HATs/HDACs is affected in Arabidopsis and maize upon changes in the degree of acetylation (Bhat et al, 2003;Tian et al, 2005). In particular, in the HAT mutant Atmcc1, characterized by histone hyperacetylation in meiosis, AtHDA7 resulted in upregulated male meiocytes (Perrella et al, 2010;Barra et al, 2012). The misregulation of the different HDACs in Athda7-2 likely affects the expression of different classes of genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the expression of HATs/HDACs is affected in Arabidopsis and maize upon changes in the degree of acetylation (Bhat et al, 2003;Tian et al, 2005). In particular, in the HAT mutant Atmcc1, characterized by histone hyperacetylation in meiosis, AtHDA7 resulted in upregulated male meiocytes (Perrella et al, 2010;Barra et al, 2012). The misregulation of the different HDACs in Athda7-2 likely affects the expression of different classes of genes.…”
Section: Discussionmentioning
confidence: 99%
“…Histone posttranslational modifications contribute to define chromatin states that drive different chromatin-based nuclear processes. In fact, histone posttranslational modifications, including acetylation, methylation, phosphorylation, and ubiquitination, control fundamental processes such as transcription (Bell et al, 2011), DNA replication (Ehrenhofer-Murray, 2004), cell cycle (O'Sullivan et al, 2010), DNA repair (Soria et al, 2012), and recombination (Perrella et al, 2010). Histone acetylation is carried out by histone acetylases (HATs), while it is erased by histone deacetylases (HDACs).…”
mentioning
confidence: 99%
“…Furthermore, additional chromatin modifiers are essential to the execution of meiotic events following meiotic S phase (Tiang et al, 2012). For instance, DNA methylation and histone H4 acetylation events contribute to chiasma distribution and frequency in Arabidopsis (Perrella et al, 2010;Yelina et al, 2012). Whether H3K9 and H3K4 methylation also contribute to the formation and repair of double-strand breaks, which underlies genetic recombination, in plant as in animal meiosis (Ivanovska and OrrWeaver, 2006;Borde et al, 2009) remains to be determined.…”
Section: Research Article Development 140 (19)mentioning
confidence: 99%
“…Recent studies in budding yeast have revealed that the chromatin mark histone 3 tri-methylated lysine 4 (H3K4me3) is associated with meiotic recombination hot spots (Borde et al, 2009). Histone acetylation is also known to influence meiotic recombination both in budding yeast and Arabidopsis (Perrella et al, 2010). We therefore performed a cytological analysis of barley meiocytes to investigate the chromatin organization in relation to chiasma distribution.…”
Section: Chiasma Localization Is Associated With Early Replicating Eumentioning
confidence: 99%